2000
DOI: 10.1103/physrevlett.85.3508
|View full text |Cite
|
Sign up to set email alerts
|

Signature of Electron-Plasmon Quantum Kinetics in GaAs

Abstract: We predict a carrier-density dependent oscillation, which is superimposed on the decay of the coherent control photon echo signal of a semiconductor. It reflects the oscillatory transfer of excitation back and forth between electrons and a mixed plasmon-phonon mode. This signature provides obvious and unique evidence for the finite duration of the interaction process, i.e., evidence for the collective Coulomb quantum kinetics. The theoretical predictions for the model semiconductor GaAs are reproduced in corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 19 publications
1
44
0
Order By: Relevance
“…The transition from the photoexcited electron-hole plasma to collective response of the many-body system takes around one period of the plasmon (less than 100 fs). Moreover, both theories and experiments of quantum kinetics have demonstrated that the LOPC modes are not established instantaneously and the coupling of two longitudinal modes is a kinetic process controlled by time and carrier density [14][15][16]. It is not surprising, however, that the delayed formation of coupled modes has no considerable influence on the observed dynamics because most of the frequency-domain measurements are incapable to resolve such short time scale.…”
Section: Introductionmentioning
confidence: 99%
“…The transition from the photoexcited electron-hole plasma to collective response of the many-body system takes around one period of the plasmon (less than 100 fs). Moreover, both theories and experiments of quantum kinetics have demonstrated that the LOPC modes are not established instantaneously and the coupling of two longitudinal modes is a kinetic process controlled by time and carrier density [14][15][16]. It is not surprising, however, that the delayed formation of coupled modes has no considerable influence on the observed dynamics because most of the frequency-domain measurements are incapable to resolve such short time scale.…”
Section: Introductionmentioning
confidence: 99%
“…[15] is numerically too demanding under these conditions. Hence, we employ a phenomenological description-with parameters based on earlier findings [15,16]. For the dephasing of the off-diagonal density matrix elements we take into account that the damping is the sum of a constant contribution due to LO-phonon scattering and a term proportional to the third root of the carrier density n [16].…”
mentioning
confidence: 99%
“…A full quantum kinetic treatment along the lines of Ref. [15] is numerically too demanding under these conditions. Hence, we employ a phenomenological description-with parameters based on earlier findings [15,16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6,7,8,11,21,39 However, there are some important differences. In the undoped system, the electronic operators commute with the collec-tive excitation (phonon) operators, and the ground state correlations can be neglected.…”
Section: 26mentioning
confidence: 99%